THE EFFECT OF FEEDING FREQUENCY AND FEEDING PERIOD ON COMMERCIAL CUT YIELD OF CROSSBRED NATIVE CHICKEN - E. F., OKTAWANTARI; SUPRIJATNA, E.; SARENGAT, W. (Majalah Ilmiah Peternakan; Vol 20 No 3 (2017): Vol 20, No 3 (2017)DO - 10.24843/MIP.2017.v20.i03.p06, 2017)
This research aims at studying the effect of feeding frequency and feeding period on commercial cut yield. The used materials were 252 unsexed (one day old chick) with 37.88 ± 1.89 g initial weight. The cage used was litter type with 36 units and 7 chicks in each unit. The experimental design was Split Plot with 4 replications, 3 levels of feeding frequency as main plot, and 3 level of feeding period as sub plot. The data collection was analyzed using 5% level of F test. It showed that there was no interaction effect between feeding frequency with feeding period (p>0.05) and in each treatments to commercial cut yield of crossbred native chicken. It can be concluded that even though the treatment did not effect on commercial cut yield, however, one time of feeding frequency within 14 hours of feeding period was the most efficient treatment applied in the experiment.